2022
DOI: 10.3390/ijms23031763
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mathematical Model of Intracellular Calcium Dynamics for Evaluating Combined Anticancer Effects of Afatinib and RP4010 in Esophageal Cancer

Abstract: Targeting dysregulated Ca2+ signaling in cancer cells is an emerging chemotherapy approach. We previously reported that store-operated Ca2+ entry (SOCE) blockers, such as RP4010, are promising antitumor drugs for esophageal cancer. As a tyrosine kinase inhibitor (TKI), afatinib received FDA approval to be used in targeted therapy for patients with EGFR mutation-positive cancers. While preclinical studies and clinical trials have shown that afatinib has benefits for esophageal cancer patients, it is not known w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…A few studies have demonstrated that afatinib may suppress cancer cell growth by inhibiting, rather than promoting (as shown in our present study) Ca 2+ signaling. Afatinib, RP4010 (an inhibitor of store‐operated Ca 2+ entry), or a combination of the two agents, could inhibit Ca 2+ oscillations and decrease viability of human esophageal carcinoma KYSE‐150 cells [19]. In PC‐9/GR cells 9 (NSCLC with EGFR T790M mutation), afatinib treatment suppressed store‐operated Ca 2+ entry and decreased cell proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated that afatinib may suppress cancer cell growth by inhibiting, rather than promoting (as shown in our present study) Ca 2+ signaling. Afatinib, RP4010 (an inhibitor of store‐operated Ca 2+ entry), or a combination of the two agents, could inhibit Ca 2+ oscillations and decrease viability of human esophageal carcinoma KYSE‐150 cells [19]. In PC‐9/GR cells 9 (NSCLC with EGFR T790M mutation), afatinib treatment suppressed store‐operated Ca 2+ entry and decreased cell proliferation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Oesophageal cancer (OC) ranks as the sixth most prevalent cause of cancer-related mortality on a global scale [ 1 ]. The signalling pathways within OC, encompassing monovalent ligands like epidermal growth factor (EGF) receptor and the complex receptor formed by the combination of the epidermal growth factor receptor (EGFR) and EGF, are of utmost importance in regulating cellular viability, proliferation and differentiation [ 2 ]. Genetic mutations frequently cause dysregulation of cancer cell signalling pathways, which in turn causes cancer cells to become resistant to treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%